St. Nicholas Collegiate Church, south transept, east wall, Joyce tomb, chest - O'Donovan, Danielle (My University, 2008)
Moulding of tomb chest, moulding comprises: freestanding fillet, double ogee. Ogees are unusual and often occur in conjuction with Flamoboyant tracery.
Joyce tomb
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Funerary Monuments; Collegiate churches; Late Medieval; moldings, ogee